Bibliometric Analysis: Parenting Program During the Worldwide Covid-19 Pandemic - Nirwana, Evi Selva; Rachmat, Irfan Fauzi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Childcare programmes have been the subject of extensive research. However, research mapping on parenting programmes during the Covid-19 pandemic is still very scarce. Therefore, the purpose of this bibliometric analysis is to compile an overview of childcare research during the Covid-19 pandemic. In this study, a total of 200 articles were collected from the Scopus database related to the theme "Parenting during Covid-19". The results of this study show that there are six clusters in the collected articles. The clusters cover various topics such as additions, articles, depressive symptoms, psychological stress, child abuse, rate of job loss, life during quarantine, as well as various aspects related to parenting during the pandemic. In addition, the second figure shows that these articles were mainly published in 2021. The third figure shows various terms related to parenting during the Covid-19 pandemic such as ADHD, loneliness, psychological stress, and job loss.